Japanese knotweed (Fallopia japonica): an analysis of capacity to cause structural damage (compared to other plants) and typical rhizome extension - Fennell, Mark (PeerJ, 2018)
Fallopia japonica (Japanese knotweed) is a well-known invasive alien species in the UK and elsewhere in Europe and North America. The plant is known to have a negative impact on local biodiversity, flood risk and ecosystem services; but in the UK it is also considered to pose a significant risk to the structural integrity of buildings that are within seven m of the above ground portions of the plant. This has led to the presence of the plant on residential properties regularly being used to refuse mortgage applications. Despite the significant socioeconomic impacts of such automatic mortgage option restriction, little research has been conducted to investigate this issue. The ‘seven-m rule’ is derived from widely adopted government guidance in the UK. This study considered if there is evidence to support this phenomenon in the literature, reports the findings of a survey of invasive species control contractors and property surveyors to determine if field observations support these assertions, and reports a case study of 68 properties, located on three streets in northern England where F. japonica was recorded. Additionally, given the importance of proximity, the seven-m rule is also tested based on data collected during the excavation based removal of F. japonica from 81 sites. No support was found to suggest that F. japonica causes significant damage to built structures, even when it is growing in close proximity to them and certainly no more damage than other plant species that are not subject to such stringent lending policies. It was found that the seven-m rule is not a statistically robust tool for estimating likely rhizome extension. F. japonica rhizome rarely extends more than four m from above ground plants and is typically found within two m for small stands and 2.5 m for large stands. Based on these findings, the practice of automatically restricting mortgage options for home buyers when F. japonica is present, is not commensurate with the risk.